2008
DOI: 10.1590/s1516-89132008000100012
|View full text |Cite
|
Sign up to set email alerts
|

Morphoagronomic genetic diversity in american wild rice species

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 9 publications
3
21
0
1
Order By: Relevance
“…The non-significant traits were flag leaf width, culm diameter and the ratio culm/width of the grain. Veasey et al (2008) also found significant differences and high variability for 11 populations of O. glumaepatula, mainly for the characters number of tillers, plant height at flowering, leaf length and width, culm length, days to heading, panicle number, panicle height, flag leaf length, spikelet length and awn length.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The non-significant traits were flag leaf width, culm diameter and the ratio culm/width of the grain. Veasey et al (2008) also found significant differences and high variability for 11 populations of O. glumaepatula, mainly for the characters number of tillers, plant height at flowering, leaf length and width, culm length, days to heading, panicle number, panicle height, flag leaf length, spikelet length and awn length.…”
Section: Resultsmentioning
confidence: 86%
“…White (65 %) and purple (35 %) genotypes were observed for SC, while presence (76 %) and absence (24 %) of the pubescence were found in GP. Veasey et al (2008) reported variation within and among populations of O. glumaepatula for stigma color, with three populations 100 % white, four populations 100 % purple, and the others with varying degrees for each color, while white was the only color found on the other South American wild rice species (O. latifolia, O. grandiglumis and O. alta).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As the study of genetic diversity of morphological traits can directly provide information on germplasm richness and provide important information for farmers or breeders especially when the resource population is large, using morphological traits to study genetic diversity is considered as a very simple and economical approach. Therefore, this classical method continues to be extensively employed in the evaluation of germplasm resources (Li et al 2001;Hien et al 2007;Veasey et al 2008). At present, in evaluating crop germplasm resources, qualitative traits such as morphological features could be readily distinguished and identified, and quantitative traits have large differences (Horejsi and Staub 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Veasey et al (2008) e Rosa et al (2006) afi rmam que trabalhos que visem a caracterização morfofenológica e agronômica das populações de espécies silvestres de arroz constituem uma lacuna a ser preenchida. Trabalhos com essa abordagem, além de caracterizar melhor essas espécies, são importantes em etapas iniciais de projetos de melhoramento, com o intuito de desenvolver populações com potencial agronômico em caracteres como produção, hábito de crescimento, altura da planta, resistência a pragas, entre outras.…”
Section: Introductionunclassified